2001
DOI: 10.1097/00007632-200109150-00012
|View full text |Cite
|
Sign up to set email alerts
|

Dural Tears in Lumbar Burst Fractures With Greenstick Lamina Fractures

Abstract: It is not possible to detect dural tear and nerve root entrapment in greenstick lamina fracture before surgery. Therefore, if there is any suspicion of such an occurrence, it should be the rule to begin with posterior approach and use the open book technique to expose the dura safely before any reduction maneuver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
13

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 13 publications
0
30
0
13
Order By: Relevance
“…The reported rate of laminar fractures ranged from 43% to 50%. 26,28,30 In 6.7% of patients of Cammisa with dural laceration, neural elements were entrapped between the fragments from the lumbar laminar fracture, but they did not report the neurologic outcome. 28 Karaikovic 31 did not report any dural tear or nerve entrapment in 110 patients had from burst fractures, who were operated with Kaneda device, although they included greenstick lamina fracture.…”
Section: Discussionmentioning
confidence: 99%
“…The reported rate of laminar fractures ranged from 43% to 50%. 26,28,30 In 6.7% of patients of Cammisa with dural laceration, neural elements were entrapped between the fragments from the lumbar laminar fracture, but they did not report the neurologic outcome. 28 Karaikovic 31 did not report any dural tear or nerve entrapment in 110 patients had from burst fractures, who were operated with Kaneda device, although they included greenstick lamina fracture.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that when there is a laminar fracture with neural entrapment, the posterior fat pad signals disappear on computed tomographic scan and magnetic resonance image. 6 In addition, preoperative neurological defi cit in patients with concomitant laminar fracture has a 100% sensitivity and 74% specifi city for the prediction of dural laceration. 7 Of patients with a dural tear, 36% to 44% will have nerve entrapment identifi ed intraoperatively.…”
Section: Resultsmentioning
confidence: 99%
“…7 , 8 This also implies that the cause of the neurological defi cit in these patients is more related to the nerve roots entrapment through the laminar fracture rather than neural compression from the retropulsion. 6 Therefore, repair of the damaged fi bers may be as important as decompression. Because greenstick lamina fracture is frequently neglected, it is important for surgeons to look for it on the preoperative images.…”
Section: Resultsmentioning
confidence: 99%
“…According to the study of Aydinli et al, 11 a 20% increase in the IP distance results in a 79% probability of greenstick laminar fractures. Many investigators have found that a burst fracture with an associated laminar fracture was 100% sensitive and 74% specific for the presence of a dural tear.…”
Section: Discussionmentioning
confidence: 96%